2015
DOI: 10.1007/s13105-015-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 causes a decrease in coronary flow in diabetic mice. The possible role of PGE2 and dysfunctional vasodilation mediated by prostacyclin receptor

Abstract: Several lines of evidence suggest that cyclooxygenase-2 (COX-2) activity can have a beneficial role in the maintenance of vascular tone of the blood vessels in diabetes. Specifically, the increased production of prostacyclin (PGI2) and prostaglandin E2 (PGE2), mediated by COX-2, has been suggested to compensate for decreased synthesis of nitric oxide (NO). The study investigates whether inhibition of COX-2 may reduce the coronary flow in diabetic animals and may also lead to decreased synthesis of prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Firstly, the selective EP 4 receptor antagonist L1613982 significantly increased the contractile effect of H 2 O 2 in coronary arteries from obese but not from lean rats suggesting the involvement of PGE 2 in the COX-2-mediated endothelial relaxant effects . This was further supported by the enhanced coronary vasodilator effect found for the selective EP 4 receptor agonist TCS 2519 in OZR and confirmed by the augmented COX-2-mediated release of PGE 2 in coronary arteries from obese rats compared with the lean controls, as reported in diabetic mice (Przygodzki et al, 2015). Hence, COX-2 derived PGE 2 acting on vasorelaxant EP 4 receptors might have a protective role against oxidative damage induced by ROS in coronary arteries under conditions of obesity-associated insulin resistance, consistent with the protective role recently ascribed to the EP 4 receptor in obesity-related inflammation (Yasui et al, 2015) and with reports showing that VSM-specific EP 4 receptor deletion exacerbates oxidative and renal injury induced by angiotensin II in mice (Thibodeau et al, 2016).…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…Firstly, the selective EP 4 receptor antagonist L1613982 significantly increased the contractile effect of H 2 O 2 in coronary arteries from obese but not from lean rats suggesting the involvement of PGE 2 in the COX-2-mediated endothelial relaxant effects . This was further supported by the enhanced coronary vasodilator effect found for the selective EP 4 receptor agonist TCS 2519 in OZR and confirmed by the augmented COX-2-mediated release of PGE 2 in coronary arteries from obese rats compared with the lean controls, as reported in diabetic mice (Przygodzki et al, 2015). Hence, COX-2 derived PGE 2 acting on vasorelaxant EP 4 receptors might have a protective role against oxidative damage induced by ROS in coronary arteries under conditions of obesity-associated insulin resistance, consistent with the protective role recently ascribed to the EP 4 receptor in obesity-related inflammation (Yasui et al, 2015) and with reports showing that VSM-specific EP 4 receptor deletion exacerbates oxidative and renal injury induced by angiotensin II in mice (Thibodeau et al, 2016).…”
Section: Figuresupporting
confidence: 58%
“…These results support previous studies in our laboratory showing that an up‐regulation of COX‐2 was associated with the enhanced basal COX‐2‐mediated relaxation in coronary arteries from OZR (Sánchez et al , ). Also in type 2 diabetic patients (Szerafin et al , ) and mice (Przygodzki et al , ), COX‐2 inhibition reduced endothelium‐dependent relaxations of coronary arterioles and blunted basal coronary blood flow, respectively, suggesting an increased release of COX‐2‐derived vasodilator prostanoids likely to compensate for abnormal vascular function in the insulin resistant states of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,17,18 We have previously reported that CPB is associated with impairment of peripheral arteriolar endothelial function in patients after cardiac surgery. 10,11,14 In particular, the relaxation responses of skeletal muscle microvessels to endothelium-dependent and independent vasodilators, ADP, substance P and SNP were significantly decreased after CPB and cardiac surgery. 10,11,14 In the present study, we found that the relaxation response of the skeletal muscle arterioles to the endothelium-dependent vasodilator bradykinin was also impaired in patients after CPB and cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14 In particular, the relaxation responses of skeletal muscle microvessels to endothelium-dependent and independent vasodilators, ADP, substance P and SNP were significantly decreased after CPB and cardiac surgery. 10,11,14 In the present study, we found that the relaxation response of the skeletal muscle arterioles to the endothelium-dependent vasodilator bradykinin was also impaired in patients after CPB and cardiac surgery. In this study, we observed that impaired relaxation response to bradykinin was more pronounced in the DM patients than the ND patients after CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Despite obtaining the image before other data were collected, to avoid confounding factors of handling, the change in ocular temperature was increased in placebo treated controls in comparison to those treated with an NSAID during the initial 24 h period. This effect may be a result of the activity of an NSAID to inhibit prostaglandin production potentially resulting in alterations of peripheral blood flow (Przygodzki et al, 2015).…”
Section: Infrared Thermography: Ocularmentioning
confidence: 99%